2016
DOI: 10.1177/1556264616665760
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Community Representation

Abstract: Although community advisory boards (CABs) are widely used in clinical research, there is limited data regarding their composition and structure, especially in Africa. Our research provides the first qualitative study of the membership practices, selection methods, and qualifications of the six major HIV research centers that comprise the Ugandan National CAB Network (UNCN). Researchers conducted interviews ( n = 45) with CAB members and research liaisons at each of the sites. While selection practices and demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…However, while community advisory boards are an important tool for assuring that clinical research is community-engaged (Lawrence & Stewart, 2016), few studies specifically speak about the diversity of community advisory boards and their ability to adequately address issues of diversity and identity representation. Furthermore, community advisory boards often do not go far enough in addressing specific issues related to diversity and equity that are needed in autism research and intervention development.…”
Section: Using a Community Advisory Board Framework To Inform Diversi...mentioning
confidence: 99%
“…However, while community advisory boards are an important tool for assuring that clinical research is community-engaged (Lawrence & Stewart, 2016), few studies specifically speak about the diversity of community advisory boards and their ability to adequately address issues of diversity and identity representation. Furthermore, community advisory boards often do not go far enough in addressing specific issues related to diversity and equity that are needed in autism research and intervention development.…”
Section: Using a Community Advisory Board Framework To Inform Diversi...mentioning
confidence: 99%
“…The use of community advisory boards (CAB) to engender good, ethical practices in health research in resource-constrained settings is well-known and accepted (Lawrence & Stewart, 2016; Manda-Taylor, 2013; Mwinga & Moodley, 2015; Nyirenda et al, 2017). Some of their functions include serving as volunteers to provide a bridge between the community and researchers by providing information to the community about the study goals, including information on their rights in research to help improve the informed consent process.…”
Section: Best Practicesmentioning
confidence: 99%
“…In this way, CABs provide bi-directional feedback between researchers and the community. Thus, CABs help to build mutually beneficial relationships between the researcher(s) and the communities in which the clinical trial is being implemented [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most of the available studies have been done on individual or study specific CABs [ 32 ]. Only one study was identified to have investigated membership practices, selection criteria, qualifications, and challenges of CABs at six Ugandan HIV clinical research institutions [ 9 ]. Yet CAB members were observed not able to critically evaluate studies for the presence of exploitative elements in Bangkok, Thailand [ 16 ].…”
Section: Introductionmentioning
confidence: 99%